Strategic decision-making and social skills: Integrating behavioral economics and social cognition research - Johannes Leder; Leonhard Schilbach; Andreas Mojzisch (International Journal of Financial Studies, 2016)
Strategic decisions are affected by beliefs about the expectations of others and their possible decisions. Thus, strategic decisions are influenced by the social context and by beliefs about other actors' levels of sophistication. The present study investigated whether strategic decision-making, as measured by the beauty contest game, is associated with social skills, as measured by the Autism Quotient (AQ). In line with our hypothesis, we found that social skills were positively related to successful strategic decision-making. Furthermore, results showed a curvilinear relationship between steps of reasoning in the beauty contest game and social skills, indicating that very high as well as very low scoring individuals on the social skills subscale of the AQ engaged in high-levels of strategic thinking.
Keywords: C72; D03; D83; 330; strategic decision-making; beauty contest game; social skills; behavioral economics